Interactions between lexical and syntactic L1-L2 overlap: Effects of gender congruency on L2 sentence processing in L1 Spanish-L2 German speakers. (1st November 2022) - Klassen, Rachel; Kolb, Nadine; Hopp, Holger; Westergaard, Marit
Abstract: Bringing together lines of research from sentence processing and lexical access, this empirical study investigates the interplay between lexical (grammatical gender) and syntactic (word order) cross-linguistic overlap in L2 German. Eighty-six L1 Spanish-L2 German and thirty-six monolingual German adults completed a German self-paced reading task with noun phrases (NPs) manipulated by L1-L2 gender congruency (congruent, incongruent, neuter) and L1-L2 adjective-noun word order (pre- vs. postnominal adjectives). The study examines the effects of gender congruency, the type of L1-L2 gender mapping (i.e., presence vs. absence of each class in L1 and L2), and L2 proficiency level. Results show that the detection of ungrammatical word order in L2 German interacts with gender congruency, in that L2 speakers are only sensitive to word order violations for sentences with gender-congruent nouns. The detection of ungrammaticality for sentences containing gender-incongruent nouns only emerges at higher L2 proficiency levels. These findings underscore the role of cross-linguistic lexical overlap in syntactic processing.